2015
DOI: 10.15761/cogrm.1000122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high–risk human papillomavirus in women from turkey

Abstract: Objectives: Data on the seroprevalence of Human papillomavirus (HPV) in Turkey are limited. The aim of this study was to characterize the high risk types of HPV in cervical cytology specimens of women in Turkey during routine cervical cancer screening. Methods:Women aged 30 years and older who had been admitted to Tepecik Education and Research Hospital in İzmir province for routine cervical cancer screening between June 2012 and December 2014 were enrolled to the study. Cervical swab samples were collected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…Some studies have been performed to evaluate the prevalence and genotype of HPV in Turkey, most of which are based on small samples. The prevalence of HR-HPV was reported to be 33.5%, 36.3%, 8.5%, 10.07%, 23.9%, and 2.79% in their studies, respectively (Aydogan et al, 2018, Alacam et al, 2021, Akcali et al, 2013, Bayram et al, 2015, Eroglu and Asgin 2020, Kulhan et al, 2017. In a study conducted on 2234 Turkish women, HPV positivity was found 38.05%, and the most common type was HPV 16 (Hancer et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have been performed to evaluate the prevalence and genotype of HPV in Turkey, most of which are based on small samples. The prevalence of HR-HPV was reported to be 33.5%, 36.3%, 8.5%, 10.07%, 23.9%, and 2.79% in their studies, respectively (Aydogan et al, 2018, Alacam et al, 2021, Akcali et al, 2013, Bayram et al, 2015, Eroglu and Asgin 2020, Kulhan et al, 2017. In a study conducted on 2234 Turkish women, HPV positivity was found 38.05%, and the most common type was HPV 16 (Hancer et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, hrHPV prevalence was found to be 1.2% in cases with normal cytology results and 7.5% in general population and 73.4% in cases with abnormal cytology. In other studies in which hrHPV subtypes were evaluated in our country, this rate ranges between 3.4% and 33.7% (5,(11)(12)(13)(14)(15). The reason for this wide range is that instead of general population, HPV was studied in cases in which the cervical anomaly is detected with smear in the majority of the studies.…”
Section: Discussionmentioning
confidence: 74%
“…With the exception of three of the studies in our country, including our study, the most common type was found to be HPV 16. This is followed by HPV 18, 31, and 51 (5,6,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Of the three studies with different findings, the most common HPV type was found to be HPV 18 in two studies and HPV 66 in one study (4,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizdeki HPV prevalansını ve genotip dağılımlarını sunan çalışmalar, farklı coğrafi bölgelerde ve zaman aralıklarındaki verileri içermektedir. Ülkemizde yapılan HPV tarama sonuçlarına ait bazı çalışmalar ise Tablo 2'de sunulmuştur (13,(16)(17)(18)(19)(20) . Ancak, HPV analizinde ve genotiplendirmede kullanılan test metotlarındaki farklılıklar elde edilen verilerin analizini güçleştirmektedir.…”
Section: Discussionunclassified